[Different drums ; Dapithapon ; Dancing attorneys [videorecording] - Lazaro, Cheche (The Probe Team, 1991)
Military story focusing on the latest peace initiative offered by the government to rebel soldiers led by ex-Lt. Col. Gregorio Honasan. A story about how people who are growing old cope with living alone. Attorneys teaching ballroom dancing and providing a dancing escort service for a fee.